Transseptal chordal replacement: early experience - Rogers, Jason H.; Bolling, Steven F. (Annals of Cardiothoracic Surgery, 2020)
Chordal replacement is a fundamental technique used in the surgical repair of primary mitral regurgitation, and can be an effective means of preserving the native valve without leaflet resection. Surgical chordal replacement can be challenging since it is performed on an open, non-beating heart, and choosing the correct chord length to restore the zone of coaptation requires both intuition and skill. Developing transcatheter, transfemoral, and transseptal approaches to mitral valve chordal replacement presents the opportunity for safer and potentially earlier treatment of patients with primary mitral regurgitation. In particular, transcatheter methods will allow adjustment of chordal length and position real-time on a beating heart under echocardiographic guidance. In this manuscript, we review the current transcatheter transseptal technologies in development and discuss the various issues related to device design, efficacy, durability, and clinical trial design.